Estrogen and viral infection - Wei, Xiangrui; Hong, Longyan; Liang, Hao; Ren, Ke; Man, Wenqing; Zhao, Yinghui; Guo, Pengbo (Frontiers in Immunology, 2025)
Gender differences exist in the susceptibility, incidence, progression, and prognosis of diseases caused by viral infections. These differences are influenced by various factors, including lifestyle and habits between males and females. Some reports have pointed out that estrogen plays an important immune-modulatory role in many viral infections. In certain viral infections, estrogen exhibits a protective and regulatory effect, while in others, it has a synergistic and promoting effect. The action of estrogen and its receptors affect the occurrence and prognosis of viral infections to some extent. This article reviews the correlation and the related mechanisms between estrogen and viral infections.